Stages of destruction and elastic compression of granular nanoporous carbon medium at high pressures - Neklyudov, I.M.; Ledenyov, O.P.; Bobrova, N.B.; Chupikov, A.A. (Вопросы атомной науки и техники, 2015)
The granular nanoporous carbon medium, made of the cylindrical coal granules of the adsorbent of СКТ-3, at an influence by the high pressures from 1 MPa to 3 GPa has been researched. The eight consecutive stages of the material’s specific volume change, which is characterized by a certain dependence of the volume change on the pressure change, have been registered. It is shown that there is a linear dependence on the double log-log plot of the material’s specific volume change on the pressure for an every stage of considered process. The two stages are clearly distinguished: a stage of material’s mechanical destruction, and a stage of elastic compression of material without the disintegration of structure at a nano-scale. The hysteresis dependence of the material’s specific volume change on the pressure change at the pressure decrease is observed. The small disperse coal dust particles jettisoning between the high pressure cell and the base plate was observed, resulting in the elastic stress reduction in relation to the small disperse coal dust particles volume. The obtained research data can be used to improve the designs of air filters for the radioactive chemical elements absorption at the NPP with the aims to protect the environment.